Two new and one newly recorded species of Anomala Samouelle, 1819 Coleoptera: Scarabaeidae: Rutelinae) from Yunnan, China - Huang, Gui-Qiang; Wang, Fa-Lei (Zootaxa, 2019)
Two new species, Anomala qiului Huang & Wang, new species and Anomala xuhaoi Huang & Wang, new species, are described and illustrated from Yunnan, China. Anomala trochanterica Arrow, 1917 is recorded from China for the first time, with the report of its intraspecific variation also discussed. Color plates (habitus and genitalia) of A. flavipunctuata Lin, 1999, A. flavoguttata Miyake, 2000, A. fuscicauda Lin, 1999 and A. trochanterica are provided for the first time.